Identification of a Human Anti-Alpha-Toxin Monoclonal Antibody Against Staphylococcus aureus Infection - Liu, Fangjie; Guan, Zhangchun; Liu, Yu; Li, Jingjing; Liu, Chenghua; Gao, Yaping; Ma, Yuanfang; Feng, Jiannan; Shen, Beifen; Yang, Guang (Frontiers in Microbiology, 2021)
Staphylococcus aureus is a major pathogenic bacterium that causes a variety of clinical infections. The emergence of multi-drug resistant mechanisms requires novel strategies to mitigate S. aureus infection. Alpha-hemolysin (Hla) is a key virulence factor that is believed to play a significant role in the pathogenesis of S. aureus infections. In this study, we screened a naïve human Fab library for identification of monoclonal antibodies targeting Hla by phage display technology. We found that the monoclonal antibody YG1 blocked the Hla-mediated lysis of rabbit red blood cells and inhibited Hla binding to A549 cells in a concentration-dependent manner. YG1 also provided protection against acute peritoneal infection, bacteremia, and pneumonia in murine models. We further characterized its epitope using different Hla variants and found that the amino acids N209 and F210 of Hla were functionally and structurally important for YG1 binding. Overall, these results indicated that targeting Hla with YG1 could serve as a promising protective strategy against S. aureus infection.